Diamond‐coated three‐dimensional GaN micromembranes: Effect of nucleation and deposition techniques. Issue 11 (1st October 2015) - Izak, Tibor; Vanko, Gabriel; Babchenko, Oleg; Potocký, Štěpán; Marton, Marian; Vojs, Marian; Choleva, Pavlina; Kromka, Alexander
Abstract : In this work, we present technological issues in the deposition of polycrystalline diamond films as a backside heat spreader for GaN membranes. We compared three nucleation techniques, including standard ultrasonic seeding by diamond powder (DP) in deionized water, drop‐off technique with DP in solution and polymer based nucleation by polyvinyl alcohol (PVA) polymer composite containing fine grained DP. The diamond growth was performed in a hot filament or microwave plasma chemical vapor deposition system. We found that standard nucleation techniques (ultrasonic seeding or immersing in diamond powder solution) resulted in damaging or cracking of GaN membranes, or low nucleation efficiency in the Z‐depth of the structures. Implementation of a novel nucleation technique with PVA polymer composite containing diamond powder led to coating of both bottom and top parts of the membrane including side walls. The coverage homogeneity was evaluated by scanning electron microscopy and Raman spectroscopy. The obtained results indicate that the efficiency (and/or nucleation density) of the polymer‐based technique is comparable with standard ultrasonic seeding and could be used in preference for nucleation of soft and fragile substrates.